Waveguides of defect chains in photonic crystals - V. Yannopapas; A. Modinos; N. Stefanou (Physical Review B, 2002)
We develop a two-stage multiple-scattering formalism for the calculation of photonic bands generated by chains of defects in photonic crystals consisting of nonoverlapping spheres, and for the calculation of the transmission of light through straight and bent waveguides of such chains. We apply the method to a specific example which demonstrates that transmission through a bent waveguide occurs with the same efficiency as for a straight waveguide.